Exercise: A Protective Measure or an "Open Window" for COVID-19? A Mini Review - João B. Ferreira-Júnior; Eduardo D. S. Freitas; Suene F. N. Chaves (Frontiers Media S.A., 2020)
The coronavirus disease 2019 (COVID-19) has spread to at least 115 countries and caused an alarming number of deaths. The current outbreak has lead authorities from many countries to adopt several protective measures, including lockdown and social distancing. Although being a reasonable measure to counteract the COVID-19 contamination, the restrictive measures have limited individual's ability to perform exercise outdoors or in gyms and similar facilities, thus raising the risks for chronic health conditions related to a sedentary lifestyle. The recent exercise recommendations to counteract the potential deleterious effects of COVID-19-related lockdown have not fully addressed resistance exercise interventions as potential home-based exercise strategies. Additionally, the following questions have been constantly raised: (1) Is training status capable of protecting an individual from COVID-19 infection?; and (2) Can a single endurance or resistance exercise session acutely increase the risks for COVID-19 infection? Therefore, the current mini review aimed to focus on these two concerns, as well as to discuss the potential use of practical blood flow restriction and no load resistance training as possible resistance exercise strategies that could be performed during the current COVID-19 pandemic.